The The impact of board independence on earnings management - Manish Bansal (STIE Malangkucecwara, 2022)
The study aims at investigating the association between family firms and earnings management through an advanced panel data regression model-Hybrid model that control for unobserved cross-sectional heterogeneity across firms and time, while estimating the coefficient of dichotomous variable - family firms. Further, the statutory backup of board independence in India provides unique setting to investigate the moderating role of board independence on the association between family firms and earnings management. Based on a sample of 2074 Bombay Stock Exchange (BSE) listed firms, spanning over 13 years from 2005 to 2017, the empirical results show that family firms are less likely to be engaged in earnings management in comparison to their non-family counterparts. Besides, results show that that board independence has constraining (liberating) effect on earnings management practices of non-family (family) firms, implying that a common board independence regulation does not strengthen the mechanism of internal corporate governance for all categories of firms. Hence, separate statutory provisions should be made for family and non-family firms to curb this corporate misfeasance. These results are robust to the alternative specification of earnings management.